Artificial Intelligence in Psychosocial Counselling : An Empirical Study of Mental Health Professionals’ Attitudes Toward AI Integration - Pazer, Sora (Journal of Techno-Social, 2024)
This study explores mental health professionals' attitudes toward integrating artificial intelligence (AI) in psychosocial counseling. Using a quantitative survey approach, we examine variables such as perceived utility, comfort with AI tools, data privacy concerns, and anticipated impacts on therapeutic practice. Findings reveal both enthusiasm for AI's diagnostic capabilities and significant apprehensions regarding data security and ethical implications. The study underscores the need for targeted training and regulatory measures to ensure the ethical use of AI in mental health contexts.